Association between severity of benign prostate hyperplasia and erectile dysfunction in two largest urology center in Pahang, Malaysia - Mohd Saiful, Mohammad Irsyadiee; Hashim, Mohammad Hamzi; Mohd Sufian, Mohammad Arif Rukaini; Ab Rashid, Islah Munjih; Salauddin, Syahril Anuar; Hj Ghazali, Hamid (Universiti Sultan Zainal Abidin, 2024)
Abstract Benign Prostate Hyperplasia (BPH) and Erectile Dysfunction (ED) are diseases that always bothering male > 40 years old. Both diseases are usually presented concurrently. Aim of the study is to determine association of BPH and ED, by measuring International Prostate Symptom Score (IPSS) and International Index of Erectile Function (IIEF-5) score. Uroflowmetry (Qmax), Prostate Specific Antigen (PSA) and prostate weight (PW) were be measured as well to look for the correlation with severity of BPH. A prospective study was conducted at 2 urology center in Pahang, Malaysia (Hospital Tengku Ampuan Afzan and Sultan Ahmad Shah Medical Center@IIUM), from 1st November 2022 until 30th of April 2023. Patient was assessed using IPSS and IIEF, as well as Qmax, PSA and prostate weight (PW). Total of 510 met the inclusion criteria and completed the study. The mean age group was 65.79 years old (65.23-66.35 years old). There were 68.2% Malay, 27.8 % Chinese, Indian 3.7 % and Orang Asli 0.2 %. Patient then labelled according to severity of Lower Urinary Tract Symptom (LUTS). Patient had IPSS score less than 8, it will be labelled as ‘No LUTS’ [18]. IPSS 8 and above will be labelled as ‘LUTS’ [18]. There were 271 patients or 53.1% of the subjects had ‘LUTS’, whereas there were 239 patients or 46.9% had ‘No LUTS’. Patient had ED was categorized for patient who had IIEF-5 score less than 17 (<17). Patient with LUTS had ED 57.9%, whereas patient had no LUTS had ED was 42.1%. Pearson chi square calculated, p value <0.0001, which is statically significant. The prevalence of ED from the study was 78.6%. Prostate weight (PW) mean 52.17g with median of 51.0 g. The association between PW and LUTS is statistically significant, p value < 0.001. Prostate Specific Antigen (PSA) mean 3.43 ng/dl with median 2.6 ng/dl. The association between PSA and LUTS is not statically significant, p value 0.003. Qmax mean 12.14 ml/s with median 11.7 ml/s. The association between Qmax and LUTS is statically significant, p value <0.001. The study have shown statistically significant between association of LUTS and ED. Qmax and prostate weight have statistically significant correlation with presence of LUTS. However, from our study, there was no correlation of PSA reading and LUTS.